Brazilian foreign policy for the war in Ukraine: changing non-alignment, counterfactual, and future perspectives - Vasconcellos de Carvalho Motta, Bárbara; Succi Junior, David Paulo [UNESP] (Taylor & Francis, 2023)
The current paper analyses the Brazilian foreign policy towards the war in Ukraine, from the tensions preceding the invasion until the first half of the war's second year. Since the conflict began, Brazil was governed by two sharply contrasting administrations, neither of which clearly aligned with one side of the conflict. It is argued, however, that while Bolsonaro assumed an inert attitude, Lula undertook a proactive non-alignment. As proposed by this forum, this article presents three counterfactuals, exploring how the Brazilian position could have been different, and outlines future perspectives based on three uncertainties: (1) will Brazil be recognized as a viable mediator? (2) will Brazil explicitly choose a side in the conflict?; (3) will Brazil continue to be engaged with this agenda?.
Keywords: Brazil; Foreign Policy; Future Scenarios; War in Ukaine